Analisis Penerapan Sistem Coretax dalam Mendukung Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi di PT X - Puji Lestari; Tresno Eka Jaya; Rochma Sudiati (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study examines how coretax is applied to Article 21 Income Tax administration and reporting at PT X, focusing on user perceptions and system performance. A qualitative case study was conducted using semi-structured interviews, closed questionnaires, observation, and document review. Four informants and twenty-two individual taxpayers with direct experience of coretax participated in the study. Interview findings were processed through data reduction, data presentation, and verification, while questionnaire responses were summarized descriptively. The findings indicate that coretax is used across employee data management, electronic withholding slip preparation, periodic tax reporting, and annual return support. Integrated tax information helps simplify administrative work and provides useful reporting data. Nevertheless, unstable access, slow response, and users' dependence on assistance remain notable obstacles. Strengthening technical reliability, service responsiveness, and practical user guidance is necessary to support more independent and accurate tax compliance.